(untitled) (Journal of Philosophy Culture and Political Science, 2022)
Changes in the external environment can have a significant transformational impact on the service sector. The crisis caused by the COVID-19 pandemic has affected all sectors of the economy, contributing to the urgency of new forms and technologies of work, including remote access and employment at home. The education system was one of the first to face global changes and the need to develop distance learning technologies for security purposes. In this regard, it is important to consider what the consequences and results of the educational process can be in a crisis. The study of changes in the education system in the context of a pandemic, the creation of a comparative assessment is important in terms of further adaptation of the education system to crisis phenomena, the development of effective technologies of remote interaction of participants in the educational process and the impact on the quality of education. Keywords: education, COVID-19 pandemic, distance learning technologies, virtual space, telecommunications, social consequences.